An Atlas of the Global Water Cycle Based on the IPCC AR4 Climate Models - Lim, Wee Ho (ANU Press, 2009)
What do climate models predict for the rainfall where you live? What about evaporation or runoff? Should your local community consider constructing new dams or do the existing water storages appear adequate? What about the availability of water for irrigation farming? Do the predictions differ between different climate models or do all the models basically predict the same changes in water availability where you live? These are all simple questions but it is surprisingly hard for an individual, whether they be a farmer, water resources engineer, teacher or interested citizen, to answer them. As researchers active in the field we could not answer the questions either. In fact, we had never seen a compilation of the rainfall, evaporation and runoff predictions made by all the different climate models. The Atlas contains maps and tables that document model predictions contributed by international climate modelling groups to the 2007 4th Assessment Report of the Intergovernmental Panel on Climate Change. The predictions are made available here via the wonders of the internet and ongoing cooperation by the international climate modelling community who routinely archive their results. The maps and tables in the Atlas document rainfall, evaporation and runoff estimates for the 20th century along with predictions of the same quantities at the end of the 21st century. Whatever your interest, we hope you find the Atlas as helpful as we do.